Increasing Production Through Local Potency-Based Feed Formulations as Alternatives to Artificial Feeds in Catfish Farming - Suryanto Hertika, Asus Maizar; Nurlaelih, Euis Elih; Shofwan, Shofwan; Putra, Renanda Baghaz Dzulhamdani Surya; Alfarisi, Muhammad Asnin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Doktor Mengabdi (DM) engages in collaborative efforts to address the issue of escalating feed costs, which result in minimal profits or even financial losses. This is intensified if, during the harvest period, the price of catfish per kilogram decreases. The imperative to address these issues is subsequently addressed through training in the development and production of self-sustaining animal feed utilizing the capabilities of indigenous components. The BUMDES of Labruk Lor Village and the